Kondisi dan Variasi Bentuk Pertumbuhan Terumbu Karang di Area Pesisir Bandara Rendani, Manokwari, Indonesia - Malyon Wanma; Jemmy Manan; Frida A Loinenak; Duaitd Kolibongso (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
Coral reefs are unique ecosystems and only occur in the tropics area. Diversity, distribution, and coral growth are influenced by environmental factors. Coral colonies morphologies or coral lifeform rates vary significantly between species and between environmental factors. This study aimed to determine the variations of hard coral based on their lifeform; and assess the condition of reefs by measuring the percent cover of live coral in the coastal area of Rendani Airport. Coral cover and coral damage data gathering used a survey approach with Point Intercept Transect (PIT) method. The results showed the variations of coral lifeform in the coastal area of Rendani was relatively low, as indicated by the absence of some coral lifeforms in the study site. The most variation lifeform was found at 7m depth with five lifeforms, while the lowest was found at 3m depth with three lifeforms. The live coral cover reached 77,66% at station 1 and 75,00% at station 2, and the lowest coverage was 11,33% at station 3. The highest average of rubble at station 1 at 4.33% and dead coral with algae was found to be highest at station 3 at 8.00%.